The Impact of Sharia Compliant Logo on Product Quality Perceptions - Dr. Anam Javeed; Dr. Muhammad Anas Rizwan (jihat-ul-islam, 2020)
Extrinsic cues displayed on the product packaging play an important role in the perception formation of consumer before the actual consumption. The logo showing the compliance of the products with Shariah laws in basically the Halal logo which is an important extrinsic cue. Among the extrinsic cues, Shariah compliant Logo is one the emerging concept in the field of consumer behavior. This study aims to analyze the moderating role of consumer knowledge on the nexus of Shariah compliant logo and perceived product quality. Using Mall intercept method, data has been collected from 504 respondents in Rawalpindi and Islamabad. Data has been analyzed using Smart PLS. Finding shows a significant and positive relationship between Shariah compliant logo and perceived product quality. However, there is no moderating role of consumer knowledge in this nexus. It can be concluded that Shariah compliant logo is considered a quality measure among the sampled consumers. These results are helpful for policy makers in marketing to develop research based marketing strategies. The finding of the study also helps to understand and extend extrinsic cues as it improves the perception of consumer about product quality which was overlooked previously. This study extends the literature of Islamic Marketing by providing empirical evidence on Shariah compliant logo as a quality perception.